Physicochemical treatment processes. - Wang, Lawrence K., ....-; Hung, Yung-Tse, ....-; Shammas, Nazih K., ....- (Totowa : Humana, 2005)
This volume serves as a basic physicochemical treatment text as well as a comprehensive reference book. It provides essential information on the physical, chemical and mechanical treatment technologies, and will also serve as a basis for advanced study or specialized investigation of the theory and practice of the individual physicochemical systems covered. It will prove invaluable to designers of water and wastewater treatment systems and civil engineers and research workers.
Keywords: Afvalverwerking